Sustainability reporting: formation, content, relevance - D.O. Seletska (Економіка, управління та адміністрування)
The article examines the concept of sustainability reporting and its evolution from the emergence of environmental threats in the 1960s to modern reporting approaches that encompass not only environmental but also social and economic aspects. Scientific research, particularly in the Web of Science and Scopus databases, demonstrates a significant increase in the number of publications on this topic from 2018 to 2023, indicating a growing interest in such reporting among both scholars and practitioners. A geographical analysis shows that this topic is actively researched in countries such as the USA, the UK, China, Australia, Italy, and India, confirming its relevance at a global level. Studies show that sustainability reporting helps businesses integrate sustainability principles into their strategies and operations, contributing to improved management efficiency and reduced negative environmental impact.